Textual health warning labels on snus (Swedish moist snuff): do they affect risk perception? - Connie Villemo Nilsen; Oddgeir Friborg; Karl Halvor Teigen; Frode Svartdal (BMC, 2018)
Abstract Background To strengthen the risk message on snus warning labels, the European Union in 2016 removed "can" from the warning "This tobacco product (can) damages your health and is addictive." We tested how these and other textual warnings affect risk perception. Methods Snus-using and non-using Norwegians aged 16-72 participated in two online survey experiments. Participants in Study 1 (N = 196) were randomized to read one of four warning labels. Outcome variables included ratings of likelihood of health damage from snus and perceived severity of such damages. Study 2 (N = 423) used similar outcome measures but added a baseline measure allowing for a pre-post comparison, as well as a control group receiving no warning label. Data were analysed using ANOVA and non-parametric tests. Results Study 1 indicated that removing "can" from the EU warning increased long-term risk perception, but adding "causes cancer" had no effect on risk perception. In Study 2, risk perception increased from pre to post, regardless of label manipulation. "Causes cancer" and "damages your health" were indicated as most alarming when participants compared and ranked all warnings. Conclusions Adding "causes cancer" or removing "can" from "damages your health" did not strengthen short-time (1 year) risk perception, but the latter increased long-term (10 years) risk perception in Study 1. In the pre-post design in Study 2, risk perception increased regardless of warning label.